Ultrasonic investigations of inclusion complexes of cyclodextrins with amphiphilic substances - further results and conclusions - Balcerzak, A. (Archives of Acoustics, 2004)
On the basis of formerly made and published [1-3] ultrasonic measurements of aqueous solutions of [ampersand]alpha;- or [ampersand]beta;-cyclodextrin with amphiphilic substances, calculations have been done and new conclusions drawn. These calculations and conclusions explain some experimental results concerning the stability of inclusion complexes of cyclodextrin with amphiphilic substances and the mechanism of the formation of such complexes.